An effective use of three renewable sources for generation of quintuple useful outputs with hydrogen for sustainable communities and greenhouses - Gursoy, Mehmet; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Global warming negatively affects societies worldwide through increased land and ocean temperatures and sea levels, which result in destroying ecosystems. In addressing these issues, building sustainable energy systems at the community level may have a pivotal impact on reducing climate change and promoting sustainability. This study focuses on the combined power process that harnesses geothermal, wind, and wave energy for several purposes, including generating electricity and heat, producing fresh water and hydrogen, and providing residential hot water. Innovatively integrating tidal energy systems with power systems ensures a dependable power supply by entirely using each renewable energy source. The proposed research entails the incorporation of various elements, such as a wind farm, a geothermal-organic Rankine cycle (ORC), a multi-effect desalination (MED) unit, an Alkaline electrolyzer, a tidal energy system, greenhouses, and a hydrogen storage and refuelling station. The thermodynamic evaluation is used to evaluate the system's efficacy under investigation. The system achieves a freshwater production rate of 2.05 kg/s and a hydrogen generation rate of 0.005 kg/s. The system's net power production is 1919.1 kW, although Heat exchanger 1 has the greatest exergy destruction rate at 2700 kW. The heat provided to the greenhouses was determined to be 7848 kW. The predominant cause of energy loss in a wind farm is availability, which accounts for 5.55 % of total energy losses. The overall energy and exergy efficiencies of the proposed system were obtained to be 18.13 % and 25.6 %, respectively. While these values may seem low due to the substantial energy inputs compared to the limited conversion into useful output, their efficiencies might be enhanced by minimizing irreversibilities and enhancing thermodynamic performance.
Keywords: Wind energy; Geothermal energy; Tidal energy; Hydrogen; Energy; Exergy; Efficiency; Greenhouse; Sustainability; SYSTEM; Thermodynamics; Energy & Fuels